Problem-Solving Ability of Seventh Grade Students Viewed From Locus of Control in Tapps Learning - Wiharno, Wiharno; Junaedi, Iwan; Rosyida, Isnaini (Unnes Journal of Mathematics Education Research, 2021)
Problem-solving ability is one of the internal factors of students that can affect mathematics learning achievement. This study aimed to describe students' problem-solving ability pattern based on Locus of Control on Think Aloud Pair Problem Solving (TAPPS) learning model. This study used mixed method with concurrent embedded design. This study subjects were seventh grade students of SMP Negeri 2 Jatibarang Brebes. Class VII-A students as an experimental group and class of VII-B students as a control group. Each Locus of Control category participants as qualitative study subjects. Quantitative data were tested using z-test and t-test, while qualitative data were analyzed descriptively. This study obtained data that: learning with Think Aloud Pair Problem Solving (TAPPS) model has a good quality for problem-solving abilities. Students with Internal Locus Of Control type can solve the problem properly until the re-checking stage. Students with Internal-External Locus Of Control type can solve the problem but still had difficulty at the re-checking stage. Students with External Locus Of Control type can only solve the problem at problem understanding stage, students had difficulty at planning problem-solving stage, carry out their problem-solving plans, and re-checking their answers.